HUBUNGAN KECEMASAN DAN KUALITAS TIDUR DENGAN PENINGKATAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI WILAYAH KERJA PUSKESMAS GERUNGGANG - Indriyani, Sherlly (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p03, 2023)
Increasing age in the elderly has an effect on physiological changes that cause hypertension. In 2022 the prevalence of hypertension in the elderly in Indonesia is 32,5% and in the Bangka Belitung archipelago province it is 36,2%. Anxiety and sleep quality are risk factors that can increase blood pressure in the elderly. The purpose of this study was to determine the relationship between anxiety and sleep quality with increased blood pressure in elderly hypertensives in the working area of ??the Gerunggang Public Health Center, Pangkalpinang City, in 2023. The study was conducted using a correlational design through the cross-sectional approach and the Spearman rank test with results in the form of univariate analysis and bivariate analysis. The research population was elderly people with hypertension who went to the Gerunggang Health Center. The research sample is 82 respondents. Respondents in this study were elderly people with hypertension who were selected as samples. The results of this study revealed that there is a relationship between anxiety and increased blood pressure in hypertensive elderly (p-value = 0,000; r = 0,471) and that there is a relationship between sleep quality and increased blood pressure in hypertensive elderly (p-value = 0,000, r = 0,446). Conclusion from this study, there is a significant relationship between anxiety and sleep quality with increased blood pressure in elderly hypertensives.